The Effect of Religiosity and Tax Socialization on Taxpayer Compliance With Taxpayer Awareness as an Intervening Variable - Fitri Agustina; Umaimah Umaimah (Indonesian Vocational Research Journal, 2022)
This study aims to determine the effect of religiosity and taxpayer awareness on Taxpayer Compliance With Taxpayer awareness as an intervening variabel. In this study, researchers examined taxpayer compliance at KPP Pratama Gresik by using independent variables, namely, religiosity, taxation socialization and taxpayer awareness. The population in this study were all individual taxpayers in the city of Gresik, sampling using random sampling method, and the number of samples as many as 70 respondents. This study uses a questionnaire with taxpayer respondent individuals. Tests were carried out using SEMPLS. The results showed that the religiosity and awareness of taxpayers affect taxpayer compliance, while tax socialization has no effect on taxpayer compliance. The results of the intervening test show that religiosity and tax socialization have an effect on taxpayer awareness. Taxpayer awareness is not able to mediate the relationship between religiosity to taxpayer compliance, while taxpayer awareness is able to mediate the relationship between tax socialization and taxpayer compliance.